THE RESULT OF THE CURRENT AND STEP-BY-STEP PEDAGOGICAL CONTROL METHODOLOGY IN THE COURSE OF PEDAGOGICAL RESEARCH (Eureka Journal of Language, Culture & Social Change, 2026)
One of the important tasks in the educational process is to identify and develop student’s knowledge, skills, and competencies. Pedagogical assessment is an integral part of this process, as it ensures the quality and effectiveness of education. In particular, the scientific application of various assessment methods in modern education plays a significant role in increasing students’ activity and intellectual potential.
Keywords: Step-by-step assessment, students’ knowledge level during the lesson and can adjust teaching methods, methodological system determines the relevance of the research